The trunk orientation during sprint start estimated using a single inertial sensor - Bergamini, E.; Guillon, P.; Pillet, H.; Camomilla, V.; Skalli, W.; Cappozzo, E. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Sprint start and block acceleration are two very important phases which could determine the result of a sprint. Tellez & Doolittle (1984) showed that these two phases account for 64% of the total result for a 100m sprint. Sprinters have to move from a crouch to a standing position, trying to reach their maximal velocity as fast as possible. Many authors have delved into the biomechanical factors concerning both phases (Fortier et al., 2005; Harland & Steele, 1997; Schot & Knutzen, 1992). Trunk orientation is considered by coaches one of the key elements in moving from the crouch to the upright position, however only a few studies focused specifically on this parameter. Moreover, the experimental setups used in the latter studies are quite cumbersome and limited in terms of acquisition volume (motion capture systems, high-speed cameras or optical contact time meters), therefore, they are hardly usable during everyday training sessions. Wearable inertial measurement units (IMU), that embed 3D linear acceleration and angular rate sensors (accelerometers and gyroscopes), can be effectively used to perform in-field biomechanical analysis of sprint running, providing information useful for performance optimisation and injury prevention. In particular, IMUs provide an estimate of body segment rotations relative to an inertia system of reference with one axis oriented as the gravitational field. The aim of this pilot study is to validate the use of a single IMU to estimate the trunk orientation angle in the progression plane during a sprint start from the blocks.